Live Donor Liver Transplantation With Older (≥50 Years) Versus Younger (<50 Years) Donors: Does Age Matter?. Issue 5 (May 2016) - Goldaracena, Nicolas; Sapisochin, Gonzalo; Spetzler, Vinzent; Echeverri, Juan; Kaths, Moritz; Cattral, Mark S.; Greig, Paul D.; Lilly, Les; McGilvray, Ian D.; Levy, Gary A.; Ghanekar, Anand; Renner, Eberhard L.; et al.
Abstract : Objective: To compare the outcome of adult live donor liver transplantation (LDLT) with grafts from older versus younger donors. Introduction: Using older donor grafts for adult LDLT may help expand the donor pool. However, the risks of LDLT with older donors remain controversial, and many centers are reluctant to use live donors aged 45 years or older for adult LDLT. Methods: Outcomes of patients receiving a LDLT graft from donors aged 50 years or older (n = 91) were compared with those receiving a live donor graft from donors younger than 50 years (n = 378). Results: Incidences of biliary (LDLT <50: 24% vs LDLT ≥50: 23%; P  = 0.89) and major complications (LDLT <50: 24% vs LDLT ≥50: 24%; P  = 1) were similar between both groups of recipients. No difference was observed in 30-day recipient mortality (LDLT <50: 3% vs LDLT ≥50: 0%; P  = 0.13). The 1- (90% vs 90%), 5- (82% vs 73%), and 10- (71% vs 58%) year graft survival was statistically similar between both groups ( P  = 0.075). Likewise, patient survival after 1- (92% vs 96%), 5- (83% vs 79%), and 10- (76% vs 69%) years was also similar ( P  = 0.686). Overall, donors rate of major complications (Dindo-Clavien ≥3b) within 30 days was low (n = 2.3%) and not different in older versus younger donors ( P  = 1). Donor median hospital stay in both groups was identical [LDLT <50: 6 (4–17) vs LDLT ≥50: 6 (4–14) days; P  = 0.65]. No donor death occurred and all donors had full recovery and returned to baseline activity. Conclusions: Right lobe LDLT with donors aged 50 years or older results in acceptable recipient outcome without increased donor morbidity or mortality. Potential live donors should not be declined on the basis of age alone.